Pengembangan Media Pembelajaran Board Game “Ular Tangga” Pada Materi Trigonometri Kelas X SMA - Martin Alex; Tri Buana Tirta Adi Luhur; Muhammad Rifdan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Interesting learning media can make the learning atmosphere less boring and can improve learning outcomes. The aim of this research was to develop the learning media Snakes and Ladders, which is one of the most famous types of board games throughout the world, for high school (SMA) students as a learning tool that is expected to be valid, effective and practical to use in the learning process. learning Trigonometry material. This research method uses Research Development (R&D) with the ADDIE model which is built in 5 stages: Analyze, Design, Development, Implementation, Evaluate. The subjects of this research were 40 active class X students at SMAN 93 Jakarta. This snake and ladder was developed based on student learning styles. The